Board Attributes and Earnings Quality of Listed Financial Firms in Nigeria - Oyebamiji, Oladejo Abiodun (International Journal of Business Management and Finance Research, 2017)
The study evaluated the effect of board attributes on earnings on earnings quality of listed financial firms in Nigeria. The study employed secondary data. The study population comprised all the 16 listed financial firms on the Nigerian Stock Exchange. Purposive sampling technique was adopted to select top 10 banks whose shares are consistently traded on the stock market. Data for board attributes and earnings quality were sourced from the audited financial statements of the selected firms, the Nigerian Stock Exchange Factbook over a period of 10 years (2008-2017). Collected data were analyzed using pooled ordinary least square, fixed effect and random effect estimation techniques. The result from the study showed that board independence (t=2.01, p<0.05) and board size (t=-2.08, p<0.05) had positive and negative significant relationship respectively with earnings quality while board meeting (t=-0.56, p>0.05) does not exhibit statistical significance. The study recommended that the percentage of independent non- executive directors on the board should be maintained because it was has a positive relationship with earnings quality and adequate provisions should be made not to allow for the impairment of their independence. The interests of shareholders are better protected when the board is dominated by independent outside directors as this will improve earnings quality. Board size should be kept within limit as its increase might allow for earnings management practices.